(untitled) (Proceeding of International Conference on Islamic Economics, Islamic Banking, Zakah and Waqf, 2023)
In Purwakarta Regency, employment is still fluctuating although it tends to increase. This can have an impact on the level of economic growth in Purwakarta Regency. The rate of economic growth in Purwakarta Regency fluctuates, although it tends to decrease every year. Therefore, this study aims to determine the correlational relationship between labor absorption variables and economic growth variables for 10 periods. The theory used for the labor absorption variable is Zamrowi’s theory. while the theory used for economic growth variables is the theory of the Central Bureau of Statistics. This research uses a quantitative approach with secondary data in the 2010-2020 observation period. The data used comes from BPS, Bappelitbangda and Manpower and Transmigration Office. The data analysis technique in this study is statistical analysis. The test performed is a simple linear regression test. In data processing, data testing is done with the help of SPSS software. The test results show that employment has a significant effect on the level of economic growth in Purwakarta Regency. This shows that employment can increase economic growth rates. When employment increases, economic growth will increase. Thus, increasing economic growth can be done through expanding employment opportunities so that employment can increase